2022
DOI: 10.3390/ijerph19095169
|View full text |Cite
|
Sign up to set email alerts
|

Hopelessness in Police Officers and Its Association with Depression and Burnout: A Pilot Study

Abstract: Hopelessness is a particularly critical condition and a risk factor for suicide. Many studies have reported that this condition is common in some occupations and is associated with high stress that is not properly managed. This study examined the prevalence of hopeless status (HS) in a sample of police officers (POs) and the association of hopelessness with depression, burnout, and suicidality. In total, 127 out of 231 POs participated in the survey; they were assessed with the Beck Hopelessness Scale, the Bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 104 publications
(117 reference statements)
1
4
0
Order By: Relevance
“…According to the job demand-control theory [ 11 ], employees experience hopelessness when faced with tasks of high job demand, low job control, and low social support for a long time and have no choice, eventually leading to burnout [ 12 , 13 ]. Previous study on police officers also corroborates the correlation between hopelessness and job burnout [ 14 ]. During the COVID-19 outbreak, the workload and work pressure on nurses continually increased owing to the unpredictable changes that arose, including a sharp increase in infected patients and negative public opinion.…”
Section: Introductionsupporting
confidence: 74%
“…According to the job demand-control theory [ 11 ], employees experience hopelessness when faced with tasks of high job demand, low job control, and low social support for a long time and have no choice, eventually leading to burnout [ 12 , 13 ]. Previous study on police officers also corroborates the correlation between hopelessness and job burnout [ 14 ]. During the COVID-19 outbreak, the workload and work pressure on nurses continually increased owing to the unpredictable changes that arose, including a sharp increase in infected patients and negative public opinion.…”
Section: Introductionsupporting
confidence: 74%
“…Burnout has been found to correlate with job satisfaction [14], absenteeism [15], intention to quit [3], and job performance [15]. Several studies have also reported on the negative impact of burnout on indices of psychological well-being, including depression [16][17][18], anxiety [16,18], hopelessness [19,20], and suicide ideation [21,22]. Studies investigating predictors of teacher burnout have identified gender, age, self-efficacy, and institutional support as salient factors [23].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that during the study period, the retired commander was about to be replaced by a new commander from another police organization. It should be noted that other Italian studies have investigated work-related stress in this population in relation to stress and mental health (Garbarino et al, 2012(Garbarino et al, , 2013Setti and Argentero, 2013;Magnavita, 2015, 2019;Civilotti et al, 2022) and, more generally, absenteeism (Magnavita and Garbarino, 2013) and personality traits (Garbarino et al, 2012(Garbarino et al, , 2014Chiorri et al, 2015). To our knowledge, this is the first study conducted with the goal of analyzing police officers' attitudes toward change at a time when a commander is changing.…”
Section: Police Officers: Contextual Characteristics and Resistance T...mentioning
confidence: 84%